PELATIHAN BILAL MAYIT DESA SUKA MAJU TANJUNG PURA - Muhammad Saleh; Hayatun Sabariah (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat)
The bilal deceased training is carried out with the aim of providing new understanding and knowledge to the deceased bilal in Suka Maju Village in carrying out fardhu kifayah. So far, the deceased bilal still applies the old and slow way of neglecting the corpse, so it is necessary to have new knowledge in carrying out the negation as well as bathing the body. For that it takes the deceased bilal training. In terms of community service organized by the STAI Jam'iyah Mahmudiyah campus in Suka Maju Village, Tanjung Pura, a bilal deceased training is held for the deceased bilal in Suka Maju Village, Tanjung Pura. This activity is carried out using the method of meeting with the head of Suka Maju Village and the Indonesian Mosque Council (DMI), then the training uses the lecture, discussion and practice method. The results of this activity, the deceased bilal were very enthusiastic in participating in this activity. This was proven by the discussions of the deceased bilal in honing the understanding of this training.